Rumen Degradability and In Vitro Fermentation Pattern in Concentrate Mixtures Containing Varying Levels of Moringa oleifera (Moringa) Leaves - Potu, Ramesh Babu; D, Nagalakshmi; M, Venkateswarlu; S. V., Rama Rao; B, Swathi (Indian Journal of Animal Nutrition, 2023)
A study was conducted to evaluate the in vitro gas production (IVGP), nutrient degradabilities and fermentation characteristics in concentrate mixtures containing varying levels of Moringa oleifera (moringa) leaves. The control concentrate mixture was prepared with maize grain, de-oiled rice bran, cotton seed cake and soybean meal as major ingredients. The other 7 iso-nitrogenous (20% CP) concentrate mixtures were prepared by partially replacing de-oiled rice bran and cotton seed cake with moringa (MOR) leaves at varying levels (5, 10, 15, 20, 25, 30 and 35%). The IVGP (ml/500mg DM) and in vitro dry matter degradability (%), in vitro organic matter degradability (%) and in vitro neutral detergent fibre degradability (%) gradually increased (P